2010
DOI: 10.1180/minmag.2010.074.2.241
|View full text |Cite
|
Sign up to set email alerts
|

Boron and lithium isotopic compositions as provenance indicators of Cu-bearing tourmalines

Abstract: The Li and B isotopic compositions of gem-quality Cu-bearing tourmalines were used (1) to distinguish among Paraiba tourmalines from Brazil and Cu-bearing tourmalines from Nigeria and Mozambique; and (2) to identify the likely source of Li and B for these gem-quality tourmalines. The δ11B values of tourmaline from Paraiba, Brazil, range from –42.4‰ to –32.9‰, whereas the δ11B values of Cu-bearing tourmaline from Nigeria and Mozambique range from –30.5‰ to –22.7‰ and –20.8‰ to –19.1‰ respectively. Tourmalines f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…SIMS requires a minimum of sample material with sputtered craters significantly <1 mm deep and 5À10 mm in diameter and therefore the requirement for an almost nondestructive method, which is critical in gemmology, is fulfilled by this technique. Shabaga et al (2010) reported d 11 B values ranging from an extremely low À42.4% to À19.1% and very high d 7 Li values in the range from +24.5% to +46.8%. They identified their d 11 B values as among the lowest values reported for magmatic systems and compared them to those of tourmalines from the Lavicky leucogranite published by Jiang et al (2003), although the latter (down to À37.3%) were corrected in a comment by and a reply by Jiang (2006).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…SIMS requires a minimum of sample material with sputtered craters significantly <1 mm deep and 5À10 mm in diameter and therefore the requirement for an almost nondestructive method, which is critical in gemmology, is fulfilled by this technique. Shabaga et al (2010) reported d 11 B values ranging from an extremely low À42.4% to À19.1% and very high d 7 Li values in the range from +24.5% to +46.8%. They identified their d 11 B values as among the lowest values reported for magmatic systems and compared them to those of tourmalines from the Lavicky leucogranite published by Jiang et al (2003), although the latter (down to À37.3%) were corrected in a comment by and a reply by Jiang (2006).…”
mentioning
confidence: 98%
“…Further provenance tools are required to distinguish between the three localities. Shabaga et al (2010) studied elbaite samples from all three localities using secondary ion mass spectrometry (SIMS) to analyse B and Li isotopes. They suggested using these isotope systems as provenance indicators for 'Paraíba-type' tourmaline, as the isotopic signatures they found were different for the three localities.…”
mentioning
confidence: 99%
“…Different approaches have been proposed for determination of origin. These techniques include, in part, using isotopic compositions of boron and lithium (Shabaga et al, 2010;Ludwig et al, 2011), photoluminescence spectra (Milisenda, 2018b), and laser-induced breakdown spectroscopy (LIBS) with multivariate statistics (Dutrow et al, 2019). These approaches may be helpful as additional techniques to enhance chemical fingerprinting and facilitate origin determination.…”
Section: Discussionmentioning
confidence: 99%
“…SIMS has been used for many studies in the earth sciences, including trace elements, light stable isotopes, geochronology and cosmochemistry (Fayek, 2009;MacRae, 1995;Reed, 1989), and in the cultural heritage (Darque-Ceretti and Aucouturier, 2004; Dowsett and Adriaens, 2004). For example, SIMS has been used to determine the provenance of gem minerals (Giuliani et al, 2000;Ludwig et al, 2011;Shabaga et al, 2010;Giuliani et al, 2000).…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Developing provenance tools for Cu-rich tourmalines is necessary, as their economic value partly depends on their origin. Li and B isotopes in Cu-rich tourmalines have been shown to be a suitable provenance tool (Ludwig et al, 2011; A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT Shabaga et al, 2010). Although the range in Cu isotopic composition of tourmalines from pegmatites is unknown, the range in H isotopic composition can be from -120‰…”
Section: Applicationsmentioning
confidence: 99%